2013
DOI: 10.1155/2013/138484
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Buyang Huanwu Decoction in Animal Model of Focal Cerebral Ischemia

Abstract: Buyang Huanwu Decoction (BHD) is a well-known Chinese herbal prescription for ischemic stroke. The objective of this systematic review and meta-analysis is to provide the current evidence for neuroprotective effects of BHD and its possible mechanisms in animal models of focal ischemia. A systematic literature search, through October 2012, was performed using six databases. The outcome measures assessed were infarct size and/or neurological score. Fifty-six studies with 1270 animals that met the inclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 28 publications
1
45
1
Order By: Relevance
“…Sensitivity analysis was performed by removing each study in sequence and recalculating the results, aiming to assess whether one or more studies influenced the overall results. We used funnel plots to examine asymmetry for publication bias, revealing an asymmetrical distribution of studies around the line of identity, indicating the possibility of a small indistinct study bias [27].…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Sensitivity analysis was performed by removing each study in sequence and recalculating the results, aiming to assess whether one or more studies influenced the overall results. We used funnel plots to examine asymmetry for publication bias, revealing an asymmetrical distribution of studies around the line of identity, indicating the possibility of a small indistinct study bias [27].…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…BYHWD is one of the classic formulas for post-stroke disability with intensive investigations. Several recent systematic reviews and meta-analysis studies conducted by us and others provide experimental and clinical evidence to support the application of BYHWD in the post-stroke treatments [67,68]. Although the quality of clinical trials needs to be improved, the effects of this formula on improving neurological functions have been well accepted.…”
Section: Classic Concepts and Representative Therapeutics For Stroke mentioning
confidence: 99%
“…Evidence-based investigations have found that BYHWD improves neurological deficiencies in both experimental studies and clinical trials [15-17]. Unfortunately, present reports tend to focus on a single target or pathway, and none of these studies has been able to reveal multifaceted regulatory mechanisms of BYHWD after ICH.…”
Section: Introductionmentioning
confidence: 99%